Florida's Introduced Reptiles: Green Iguana (Iguana iguana) - Paige Borcyk; Elizabeth Fortner; Natalie M. Claunch; Steve A. Johnson (EDIS, 2021)
This is one in a series of similar EDIS documents summarizing general knowledge about Florida's introduced reptiles.